PEMBERDAYAAN IBU PKK MELALUI PELATIHAN KETERAMPILAN PEMBUATAN PRODUK DARI OLAHAN PISANG - Nuriffah Amini; Srianti Permata; St. Hadijah Wahid (LPPM STAI Muhammadiyah Probolinggo, 2022)
It is very important to empower PKK women as members of the community and are still classified as productive workers. Bacu Village, Tonra Subdistrict, is a village located in the south of Tonra Subdistrict, Bone Regency, which has not been fully touched by empowerment programs on skills and entrepreneurship. The purpose of this activity is to raise awareness and independence in doing business, as well as to expand employment opportunities in order to increase family income in an effort to achieve a happy and prosperous family. The method for this service uses the method of discussion and practice. The achievement of the training is that the empowerment participants already have skills in making banana chips products, so that they can continue to produce products that have economic value independently. Keywords: empowerment of PKK, training on product making, banana chips